IDENTIFICATION OF STAKEHOLDERS AND THEIR ROLES IN ECOTOURISM HAZARD MANAGEMENT IN MOUNT RINJANI NATIONAL PARK - harini muntasib; Tri Rahayuningsih; Anisaulhaq Aminsyah (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Mount Rinjani is a volcano with hot water, savanna, and other beauty of nature as one of the leading destinations in Lombok. Behind its beauty, Mount Rinjani National Park (TNGR) is in a natural hazard area, making it a disaster-prone area. The objective of this study is to identify the parties and roles of each party involved in the Ecotourism hazard management in TNGR based on their level of interest and influence. Determination of sampling used purposive sampling, as well as semi-structured key informant interviews with snowball sampling using interview guides. The study object of this study were the parties (stakeholders) and the relationship between the parties involved in the hazard management of TNGR ecotourism. The roles of stakeholders in managing the dangers of TNGR Ecotourism were divided into four: support, actors, decision-makers, and infrastructure providers. The key players were TNGR Center and West Nusa Tenggara (NTB) Provincial Tourism Office. The subjects were North Lombok Regency Tourism Office, Central Lombok Regency Tourism Office, East Lombok Culture and Tourism Office, EMHC (Edelweiss Medical Help Center), NTB Provincial Office of Environment and Forestry, Mataram Rescue and Search Office, BPMVG Sembalun, Rinjani Porter Guide Forum, Lombok APGI, Head of Sembalun Subdistrict, Head of Bayan Subdistrict, Sangkreang Nature Lovers Organization, and Tourism Activist Group (Pokdarwis) Rinjani Perkasa. The context setter was Regional Disaster Management Agency (BPBD) of NTB Province. The crowd was NTB Regional Police (Polda), Korem (Subregional Military Command) 162 Wira Bhakti Mataram, Regional Development Planning Agency (Bappeda) of NTB Province, Ministry of Energy and Mineral Resources of NTB Province, NTB Provincial Public Works and Spatial Planning Office, Rinjani Tourism Image Forum, North Lombok TO Association, Central Lombok TO Association, East Lombok TO Association, Daily Executor Board (DPH) Geopark UGG Rinjani Lombok and Grahaphala Unram. Key words: hazard, management, Mount Rinjani, stakeholder